Antibacterial Activities and In Vitro Anti-Inflammatory (Membrane Stability) Properties of Methanolic Extracts of Gardenia coronaria Leaves - Amin Chowdhury; Shofiul Azam; Mohammed Abdullah Jainul; Kazi Omar Faruq; Atiqul Islam (International Journal of Microbiology)
This work is carried out with Gardenia coronaria leaves that belong to the family Rubiaceae, which is a small-to-medium-sized but tall, deciduous tree, 7.6–9 m high on an average. Leaves are used for the treatment of rheumatic pain and bronchitis. The leaf of the plant consists of coronalolide, coronalolic acid, coronalolide methyl ester, ethyl coronalolate acetate triterpenes (secocycloartanes), and so forth. Methanol extract from the leaves of Gardenia coronaria was completely screened for membrane stability and antibacterial activity. The lower concentrations of Methanolic leaf extract of Gardenia coronaria gave good antimicrobial and anti-inflammatory activity, but higher concentrations gave relatively more projecting antibacterial activity in vitro as compared with Kanamycin. The crude drug’s anti-inflammatory effects were compared with those of Aspirin as positive control. The Methanolic extracts of Gardenia coronaria leaves possessed a broad spectrum antibacterial activity against a variety of both Gram-negative and Gram-positive organisms like Streptococcus agalactiae, Escherichia coli, Pseudomonas aeruginosa, Bacillus cereus, Shigella sonnei, Shigella boydii, and Proteus mirabilis, with a zone of inhibition from 10 to 16 mm. The extract also showed good membrane stability to be considered as having significant anti-inflammatory action.